Excess Viscosities and Volumes of Dimethylsulphoxide + Alcohols at 298.15 K - B. Niazi, Shahida; Mahmood, Farzana; Hashim, M.; Safdar Hussain, M. (Asian Journal of Chemistry, 2010)
Excess viscosities, ηE, and volumes, VE, of dimethylsuiphoxide + methanol,ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, t-butanol andwater were computed from density data, over the whole range of compositionat 298.15 K. ηEs are negative over the entire range of compositionfor all systems except water, indicating a negative deviation from Raouit'slaw whereas VEs are positive indicating an expansion in volume. VE andηE data was fitted to polynomial function to get values of various coefficients.